WOMEN AND ORAL CONTRACEPTIVES: REFLECTIONS FOR NURSING - Arantes Elias, Elayne; Machado Guimarães, Gabriela; Ventura Ferreira, Gerusa (Cadernos ESP, 2025)
Objective: To identify the main risk factors for the use of hormonal contraceptives; To understand the main side effects of oral contraceptives; and To describe the repercussions on the lives of women using them. Methods: Research with 19 women who use hormonal oral contraceptives through individual interviews. Data were interpreted using Bardin Content Analysis. Results: Most of them were advised by a gynecologist regarding the use of contraceptives. Headache and edema were the most reported symptoms. All of them are aware of the benefits and harms of using contraceptives, but there was a lack of guidance regarding the risks of using them. Conclusion: A thorough consultation is essential, with the exercise of reproductive planning and guidance on the use, effects and risks of contraceptives, actions that can and should be performed by a nurse trained in care, communication and education in women's health.
Keywords: Women; Hormonal Contraception; Nursing